2013
DOI: 10.1155/2013/363826
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behaviour of a Highly Alloyed Austenitic Alloy UB6 in Contaminated Phosphoric Acid

Abstract: The influence of temperature ∘ C) on the electrochemical behaviour of passive films anodically formed on UB6 stainless steel in phosphoric acid solution (5.5 M H 3 PO 4 ) has been examined by using potentiodynamic curves, electrochemical impedance spectroscopy, and Mott-Schottky analysis. UB6 stainless steel in contaminated phosphoric acid is characterised by high interfacial impedance, thereby, illustrating its high corrosion resistance. The obtained results show that the films behave as n-type and p-type se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 67 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…Hydrochloric acid solutions are commonly used, for example, in pickling, industrial acid cleaning, and oil well acidifying which are all processes that destroy metals. Mild steel corrodes severely during these processes, especially with the use of hydrochloric acid, which is a terrible waste of resources and money [ 2 , 3 ]. To minimize the effect of corrosion, there has been considerable industrial and scientific interest in studying corrosion control, in order to develop new, more economical and effective compounds that are often added to the acidic solution [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrochloric acid solutions are commonly used, for example, in pickling, industrial acid cleaning, and oil well acidifying which are all processes that destroy metals. Mild steel corrodes severely during these processes, especially with the use of hydrochloric acid, which is a terrible waste of resources and money [ 2 , 3 ]. To minimize the effect of corrosion, there has been considerable industrial and scientific interest in studying corrosion control, in order to develop new, more economical and effective compounds that are often added to the acidic solution [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, all these studies have been performed in pure phosphoric acid [12][13][14] or polluted phosphoric acid, i.e.pure phosphoric acid with the addition of chloride and sulfate ions at various temperatures [3,[14][15][16][17][18][19][20][21][22][23][24]. Sanchez-Tovar et al [14,17] have shown that between 20 • C and 60 • C, the temperature had no effect on corrosion potential, passive current and passive range on AISI 316L SS in pure phosphoric acid (40 wt%).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphoric acid is an important industrial acid used mainly in fertilizer production. It has also gain preference nowadays over HCl and H 2 SO 4 acids in acid cleaning because the dissolution rate of metals in H 3 PO 4 acid is slower than in HCl and H 2 SO 4 acids [333,334]. Also, H 3 PO 4 is used in electropolishing of Al [335].…”
Section: H 3 Po 4 Environmentmentioning
confidence: 99%
“…In addition, it was found that 1200 ppm Linum usitatissimum seeds extract was effective for aluminium in 3.5% NaCl solution and inhibited the metal surface by 82% (r, s) after 24 h of immersion. pure state, the corrosivity of H 3 PO 4 is mild when compare to that of nitric or sulphuric acids but becomes aggressive when impurities like chlorides, fluorides, and sulphides are present [334]. The impurities somehow are inevitable as they are often introduced during production.…”
Section: H 3 Po 4 Environmentmentioning
confidence: 99%